Evaluating the Usability of Canva Among University Students in Pekanbaru Using the WEBUSE Method - Hidayat, Rahmat; Andriyani, Yanti; Husnah, Mirdatul; Sinaga, Irfan; Avelia, Ririn; Maisarah, Dina; Fentika, Winda; Wulandari, Nindya (Politeknik Negeri Batam, 2025)
Canva is a design platform used to create social media graphics, presentations, posters, documents, and other visual content. This study aims to evaluate user satisfaction with the web-based version of Canva using the WEBUSE method, which covers four main aspects: Content, Organization and Readability, Navigation and Links, User Interface Design, and Performance and Effectiveness. Data were collected through an online questionnaire distributed to university students in the Pekanbaru area via WhatsApp and Instagram. A total of 65 respondents were obtained through the data collection and screening process. The evaluation results show that all aspects fall into the